PENDAMPINGAN GENERASI MILENIAL DALAM PENGEMBANGAN AGROWISATA DI DESA SAMBIK BANGKOL KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA - Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman, Fathurrahman (Yayasan Nusantara Hasana Berdikari, 2024)
Sambik Bangkol is one of the villages in Gangga District, North Lombok Regency. The millennial generation is a productive group that plays a major role in planning and managing sustainable tourism. The agricultural landscape in Sambik Bangkol Village has the potential to be developed into a tourist destination (agrotourism). Based on community service activities, it can be seen that the youth in Sambik Bangkol Village, among other things: better understand agricultural resources in Sambik Bangkol Village, better understand the potential of agricultural resources in developing agroforestry in Sambik Bangkol Village, and better understand the role of the younger generation (millennials). in developing agrotourism in Sambik Bangkol Village.